A model for the coupling of the Greater Bairam and local environmental factors in promoting Rift-Valley Fever epizootics in Egypt. (January 2016) - Gil, H.; Qualls, W.A.; Cosner, C.; DeAngelis, D.L.; Hassan, A.; Gad, A.M.; Ruan, S.; Cantrell, S.R.; Beier, J.C.
Abstract: Objectives: Rift-Valley Fever (RVF) is a zoonotic mosquito-borne disease in Africa and the Arabian Peninsula. Drivers for this disease vary by region and are not well understood for North African countries such as Egypt. A deeper understanding of RVF risk factors would inform disease management policies. Study design: The present study employs mathematical and computational modeling techniques to ascertain the extent to which the severity of RVF epizootics in Egypt differs depending on the interaction between imported ruminant and environmentally-constrained mosquito populations. Methods: An ordinary differential system of equations, a numerical model, and an individual-based model (IBM) were constructed to represent RVF disease dynamics between localized mosquitoes and ruminants being imported into Egypt for the Greater Bairam. Four cases, corresponding to the Greater Bairam's occurrence during distinct quarters of the solar year, were set up in both models to assess whether the different season-associated mosquito populations present during the Greater Bairam resulted in RVF epizootics of variable magnitudes. Results: The numerical model and the IBM produced nearly identical results: ruminant and mosquito population plots for both models were similar in shape and magnitude for all four cases. In both models, all four cases differed in the severity of their corresponding simulated RVF epizootics. The four cases, ranked by the severity of the simulated RVF epizootics in descending order, correspond with the occurrence of the Greater Bairam on the following months: July, October, April, and January. The numerical model was assessed for sensitivity with respect to parameter values and exhibited a high degree of robustness. Conclusions: Limiting the importation of infected ruminants beginning one month prior to the Greater Bairam festival (on years in which the festival falls between the months of July and October: 2014–2022) might be a feasible way of mitigating future RVF epizootics in Egypt. Graphical abstract: The IBM produced four times as many infected ruminants as the numerical model. Limiting the importation of infected ruminants beginning one month prior to the Greater Bairam festival (on years in which the festival falls between the months of July and October: 2014–2022) might be a feasible way of mitigating future RVF epizootics in Egypt. Highlights: We used an individual-based model to ascertain the extent of RVF epizootics in Egypt. The model was based on interaction between imported ruminant and environmentally-constrained mosquito populations. Limiting the importation of infected ruminants beginning one month prior to the Greater Bairam festival (on years in which the festival falls between the months of July and October: 2014–2022) might be a feasible way of mitigating future RVF epizootics in Egypt.